2004
DOI: 10.1097/01.asn.0000145895.62896.98
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction Enhances Progressive Renal Damage in an Experimental Model for Cardio-Renal Interaction

Abstract: Abstract. Studied were the effects of myocardial infarction (MI) on mild renal function loss in unilateral nephrectomized (UnX) rats. UnX was performed, followed after 1 wk by a variable MI (UnX ϩ MI; n ϭ 24). Rats with only UnX (n ϭ 15) or MI (n ϭ 9) and double sham animals (CON, n ϭ 15) served as controls. Renal outcome was measured by proteinuria and plasma creatinine. Focal glomerulosclerosis (FGS) incidence was evaluated by renal histology. Cardiac function and systolic BP were measured. A division into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 32 publications
4
71
0
Order By: Relevance
“…This study confirms our previous finding that MI induces enhanced progressive renal damage in unilateral nephrectomized rats (11). This detrimental cardiorenal interaction can be attenuated by treatment with either an ACE inhibitor or a VPI, with substantial beneficial effects on kidney and heart.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This study confirms our previous finding that MI induces enhanced progressive renal damage in unilateral nephrectomized rats (11). This detrimental cardiorenal interaction can be attenuated by treatment with either an ACE inhibitor or a VPI, with substantial beneficial effects on kidney and heart.…”
Section: Discussionsupporting
confidence: 80%
“…In our previous study, we found a trend toward a decrease in natriuretic peptide levels in the group with combined cardiac and renal damage, whereas in the group with only cardiac damage, higher levels were observed (11). From this observation, we hypothesized a role for natriuretic peptides in the deteriorating effect of the cardiorenal interaction.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations